2016
DOI: 10.3138/ptc.2015-84
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Breast Cancer: A Qualitative Study on the Barriers to and Facilitators of Exercise Promotion from the Perspective of Health Care Professionals

Abstract: We determined the barriers to and facilitators of exercise promotion by health care professionals (HCPs) for women with breast cancer (BC). The study was a qualitative descriptive study. Semi-structured interviews were conducted with HCPs who treat individuals with BC in Ontario. The interviews were recorded and transcribed. Two reviewers independently used content analysis to determine codes and themes developed in the interviews. NVivo 10 was used during the coding process. A total of 24 HCPs participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…To increase levels of PA promotion towards patients with cancer, several studies tried to identify factors that influence HCPs in their PA promotion (Jones, Courneya, Peddle, & Mackey, ; Karvinen et al., , ; O'Hanlon & Kennedy, ; Park et al., ; Smith‐Turchyn, Richardson, Tozer, McNeely, & Thabane, ; Spellman et al., ; Williams et al., ). They detected factors belonging to three categories: attitudes of HCPs (both, perceived benefits and concerns), perceived patient characteristics and structural factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase levels of PA promotion towards patients with cancer, several studies tried to identify factors that influence HCPs in their PA promotion (Jones, Courneya, Peddle, & Mackey, ; Karvinen et al., , ; O'Hanlon & Kennedy, ; Park et al., ; Smith‐Turchyn, Richardson, Tozer, McNeely, & Thabane, ; Spellman et al., ; Williams et al., ). They detected factors belonging to three categories: attitudes of HCPs (both, perceived benefits and concerns), perceived patient characteristics and structural factors.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived patient characteristics have been studied almost exclusively in terms of patients’ interest in PA (Karvinen et al., , ; Park et al., ; Spellman et al., ; Williams et al., ), although other patient characteristics could influence HCPs’ PA promotion likewise. Structural factors analysed to date involved various aspects including HCPs’ working environment, their education and characteristics of the healthcare system (Karvinen et al., , ; O'Hanlon & Kennedy, ; Park et al., ; Smith‐Turchyn et al., ; Spellman et al., ; Williams et al., ). However, it needs further clarification how these structural factors affect the PA promotion to outline ways to overcome structural barriers.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research in Ontario has found that barriers at the institutional level, HCP level, and patient level may all contribute to a lack of exercise promotion. [22] For example, institutionally a lack of time with each patient, a lack of defined role for who should be discussing exercise, and a lack of funding for the inclusion of rehabilitation professionals and exercise programs were stated barriers to exercise promotion. [22] Professionally, HCPs commonly described a lack of their own specific exercise knowledge and a vast number of competing priorities needed to discuss with their patients as barriers to exercise promotion.…”
Section: Introductionmentioning
confidence: 99%
“…[22] For example, institutionally a lack of time with each patient, a lack of defined role for who should be discussing exercise, and a lack of funding for the inclusion of rehabilitation professionals and exercise programs were stated barriers to exercise promotion. [22] Professionally, HCPs commonly described a lack of their own specific exercise knowledge and a vast number of competing priorities needed to discuss with their patients as barriers to exercise promotion. [22] Finally, professionals also perceived patients with BC as having poor attitudes towards exercise, lacking accessibility to exercise resources, and having complex medical needs as patient barriers to promoting the recommended levels of exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation